Efecto de diferentes sustratos sobre la aclimatación del anturio anthurium andreanum en vivero - Maza Solano, José Fernando (2014)
On the farm of Santa Inés UTMACH in the period from September to November 2013 the effect of acclimation of vitro plants to substrates composed of materials of the region against the use of agricultural land (Anthurium andreanum Lin.) was carried on. The proposed objectives of this essay were: 1. To assess the response of anthurium plantlets acclimatization (Anthurium andraeanum Lind) to different substrat. 2 Determine the economic analysis required to acclimate anthurium. The test area corresponds to a Tropical dry forest (bms-T) with an average annual rainfall of 699 mm Moya (2004), an average annual temperature of 25 º C and a relative humidity of 84%. The materials used were plants (rooted anthurium), organic and inorganic substrates, tools, manual pump spray, surface soil, rice chaff, coffee husk, oasis, charcoal, pumice, Coir, guano, which they will be mixed in different proportions resulting five treatments. T1. Chaff rice 50% - Oasis 25%-soil surface; T2. Coffee husk- 50% coal 25% surface-soil; T2. Coffee husk- 50% coal 25% surface-soil 25%; T3 Pumice25%- 25% guano surface-soil 25%; T4 Guano 50% - Coir 25% - topsoil and T5. Conventional agricultural land 100% disinfected. Treatments were arranged in the greenhouse in a randomized block with three replications. The variables analyzed were: plant height and height growth, number of leaves per plant every 15 days, plant biomass and plant survival. Statistical analysis of the variables had highly significant treatment at all stages of analysis for plant height, number of leaves per plant and biomass, standing between treatments T4 substrate. Guano 50%, Coir 25% surface-soil 25% and T3. Pumice 25% - guano 50% manure - topsoil 25%. The increase in plant height reached up to 42 days in the nursery setting was the highest in the T1 substrates. Chaff of rice 50%- oasis 25% - topsoil 25% and T4. Guano-50% Coir 25%, topsoil 25%. Growth in vitro plant height and leaf Issuing were fit to a linear regression model with significant rates of Determination. Guano substrate T4-50% Coir 25% - soil surface reached the further development of the plants - height, leaf emission and plant biomass and survival at end of study, as well as to cost of production was also low T4.